2019
DOI: 10.1152/jn.00720.2018
|View full text |Cite
|
Sign up to set email alerts
|

A rapid visuomotor response on the human upper limb is selectively influenced by implicit motor learning

Abstract: How do humans learn to adapt their motor actions to achieve task success? Recent behavioral and patient studies have challenged the classic notion that motor learning arises solely from the errors produced during a task, suggesting instead that explicit cognitive strategies can act in concert with the implicit, error-based, motor learning component. In this study, we show that the earliest wave of directionally tuned neuromuscular activity that begins within ~100 ms of peripheral visual stimulus onset is selec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 76 publications
1
19
0
Order By: Relevance
“…In addition, participants who perform no-cursor reaches with minimal instruction or more detailed instruction (to ensure strategy wasn’t used) show similar rates and extents of learning of reach aftereffects (see OSF; https://osf.io/9db8v/ ), which is in line with some previous findings 24 , 36 . If no-cursor reach deviations reflect implicit changes in state estimation, these arise much quicker than previously thought bolstering recent claims that the earliest wave of muscle activity during adaptation is influenced by implicit motor learning 37 .…”
Section: Discussionmentioning
confidence: 74%
“…In addition, participants who perform no-cursor reaches with minimal instruction or more detailed instruction (to ensure strategy wasn’t used) show similar rates and extents of learning of reach aftereffects (see OSF; https://osf.io/9db8v/ ), which is in line with some previous findings 24 , 36 . If no-cursor reach deviations reflect implicit changes in state estimation, these arise much quicker than previously thought bolstering recent claims that the earliest wave of muscle activity during adaptation is influenced by implicit motor learning 37 .…”
Section: Discussionmentioning
confidence: 74%
“…Moreover, the fact that both stretch reflex and visuomotor feedback systems exhibit similar control policies despite different sensory inputs, perhaps only sharing the final output pathway, suggests that this simple feedback pathway may be an evolutionary old system. Indeed, several studies have suggested that visuomotor feedback is controlled via a pathway through the colliculus (Reynolds and Day (2012); Gu et al (2018); Corneil et al (2004)). Furthermore, it has been suggested that visuomotor feedback responses involve two different phases that are behaviourally different Cross et al (2019).…”
Section: Discussionmentioning
confidence: 99%
“…Following the first description in non-human primates, a number of studies have reported the existence of SLRs in humans (12,(21)(22)(23)(24). Such studies have mostly adopted arm reaching tasks, often performed in the presence of a constant force field opposing the reach direction (25), given that a sustained background EMG activity appears to enhance the detectability of SLR (21).…”
Section: 2] Slrs In Humans' Shoulder and Arm Muscles During Reaching Tasksmentioning
confidence: 99%